2016
DOI: 10.20344/amp.6998
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Compliance with a Sepsis Resuscitation Bundle in a Portuguese Emergency Department.

Abstract: <p><strong>Introduction:</strong> Severe sepsis and septic shock are common conditions with high levels of morbi-mortality surpassing those of coronary heart disease or stroke. The reality of hospital treated sepsis is largely unknown outside of the intensive care unit. We therefore aimed to evaluate the level of compliance with the Surviving Sepsis Campaign 6-hour bundle in a Portuguese emergency department and to relate it to the patient clinical outcomes. </p><p><strong>M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Other observational and quasiexperimental studies reported similar results (40,55,(78)(79)(80)(81)(82)(83)(84)(85)(86)(87)(88)(89)(90)(91)(92). When EGDT was incorporated into a clinical pathway for the treatment of severe sepsis and septic shock, hospital mortality could be decreased (93).…”
Section: Compliance With Surviving Sepsis Campaign (Ssc) Bundlementioning
confidence: 61%
“…Other observational and quasiexperimental studies reported similar results (40,55,(78)(79)(80)(81)(82)(83)(84)(85)(86)(87)(88)(89)(90)(91)(92). When EGDT was incorporated into a clinical pathway for the treatment of severe sepsis and septic shock, hospital mortality could be decreased (93).…”
Section: Compliance With Surviving Sepsis Campaign (Ssc) Bundlementioning
confidence: 61%
“…Additionally, a retrospective, observational cohort learn about performed by using Carvas et al (2016) performed in Portugal among 178 patients in ED patients using a questionnaire. The study outcomes revealed that compliance with the sepsis bundle was 62.9% for lactate measurement, 62.9% for blood cultures earlier than antibiotics, 41.6% for antibiotics in the first three hours, 76.4% for fluid administration, 25% for vasopressor administration, 37% for central venous pressure measurement and, 39% for central venous oxygen saturation measurement.…”
Section: Administer Intravenous Fluidmentioning
confidence: 99%